Evaluación de los beneficios económicos del sistema de generación de energías renovables en la guajira (2022)
Energy is indispensable for the economic growth and development of a country. The objective of this research is to evaluate the economic benefits of the renewable energy generation system in La Guajira. For the compilation of information, entities of the mining and energy sector, both public and private, as well as theses, books and scientific articles were used as references. In the methodological field, an analytical study was carried out through documentary research, and 3 development phases were established to respond to the objectives set.